(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
The present study deals with Pharmacophore based analog generation of Epicatechin derivatives against the PKC-alpha receptor for treating colon cancer. The chemical features of Epicatechin were analyzed by catalyst - Hiphop algorithm and its derivatives were generated based on Epicatechin Pharmacophore using Minimaybridge commercial database. Two different Epicatechin Pharmacophore analogs were acquired by virtual screening and docked against the PKC-alpha for screening the protein binding affinity. The Pharmacophore result gives HTS01501 possess -3.514 Kcal /mol highest dock score as like as Epicatechin.